Agriculture programs impacting food security in two HIV/AIDS-affected Kenyan and Zambian communities - Stull, Valerie Jo (Kansas State University, 2009)
HIV/AIDS is one of the most devastating health concerns of the developing world, especially in sub-Saharan Africa (SSA). To address individual food insecurity and malnutrition, numerous small-scale nutrition and agriculture interventions have been implemented. This study compared the CTC Community Garden Project in Maai Mahiu, Kenya (n=15) and the HelpMercy Nutrition and Food Security Project (seed distribution) in Macha, Zambia (n=64), after one year. Study objectives included assessing food security in Maai Mahiu, determining beneficiaries' perceived usefulness of the interventions, comparing and evaluating the interventions, determining the importance of education in the interventions, and making recommendations for improvement. A survey in Maai Mahiu used a modified FAST tool to determine food security for beneficiaries (n=15) and non-participants (n=50). The majority of respondents were determined food insecure (without hunger), indicating a need for improved access to food/land. To determine outcomes and make comparisons, intervention outcome and beneficiary 'perceived usefulness' were measured using two verbally administered surveys, two focus groups, and two interviews with translation. Qualitative and quantitative results demonstrated differences between beneficiary perceptions of the interventions. No association was observed between perceived usefulness of the two studies (χ2). A backward elimination logistic regression model of the HelpMercy intervention showed that attendance at community-based nutrition and agriculture education sessions (CBES), household size, and number of seed types planted were predictors of perceived usefulness. Households who attended at least one CBES were more likely to perceive the intervention as useful (χ2 for trend, p=0.007), and there was a linear relationship between number of CBES attended and perceived usefulness (Mann-Whitney, p=0.008). Results may support research that agriculture interventions are more effective when combined with nutrition education. Perceived barriers and benefits differed significantly between the two programs. 60.3% of HelpMercy beneficiaries and 40.0% of CTC beneficiaries perceived the interventions as useful. Program improvements are possible, and further research is needed to better understand the impact and potential benefits of small-scale nutrition and agriculture interventions for HIV-affected populations in SSA.
Keywords: HIV/AIDS; Food Security; Zambia; Kenya; Perceived Usefulness; Monitoring and Evaluation; Agriculture, General (0473); Health Sciences, Nutrition (0570)